Effect of Propafenone on the Contractile Activity of Latissimus Dorsi Muscle Isolated in an Organ Chamber: Experimental Study in Rats - Ricardo Simões (Arquivos Brasileiros de Cardiologia, 2002)
OBJECTIVE: To study the effect of propafenone on the contractile function of latissimus dorsi muscle isolated from rats in an organ chamber. METHODS: We studied 20 latissimus dorsi muscles of Wistar rats and divided them into 2 groups: group I (n=10), or control group - we studied the feasibility of muscle contractility; group II (n=10), in which the contralateral muscles were grouped - we analyzed the effect of propafenone on muscle contractility. After building a muscle ring, 8 periods of sequential 2-minute baths were performed, with intervals of preprogrammed electrical stimulation using a pacemaker of 50 stimuli/min. In group II, propafenone, at the concentration of 9.8 µg/mL, was added to the bath in period 2 and withdrawn in period 4. RESULTS: In group I, no significant depression in muscle contraction occurred up to period 5 (p>0.05). In group II, a significant depression occurred in all periods, except between the last 2 periods (p<0.05). Comparing groups I and II only in period 1, which was a standard period for both groups, we found no significant difference (p>0.05). CONCLUSION: Propafenone had a depressing effect on the contractile function of latissimus dorsi muscle isolated from rats and studied in an organ chamber.